Supply Chain Business Intelligence and the Supply Chain Performance: The Mediating Role of Supply Chain Agility - Wissawa Aunyawong; Phutthiwat Waiyawuththanapoom; Sittichai Pintuma; Phichitphol Sitthipo (International Journal of Supply Chain Management, 2020)
The study has planned to examine the impact of the supply chain business intelligence on the supply chain performance of the Indonesian firms. Additionally, the study has examined the mediating role of agile capability and supply chain capability. For data gathering, total 450 questionnaires were distributed and obtained only 325 questionnaires. During data screening process 23 questionnaires were excluded, since they were incomplete. Therefore, we obtained 67% response rate for the survey in present study. Partial Least Square-Structural Equation Modeling (PLS-SEM) is an important statistical procedure to carry out multivariate data analysis, Empirical analysis in this study supports the supply chain business intelligence competence with respect to technical, cultural and managerial competence. This indicates that it is necessary to utilize appropriate technologies and tools and have well-defined processes, although these are not sufficient conditions to develop business intelligence product efficiently and effectively, such as, relevant knowledge and information which facilitate in the decision-making functions of the supply chain. Besides, some inter- and intra-organizational culture elements also affect the business intelligence product creation. The prior research further supported the significance of knowledge/information-related competences to enhance agile performance characteristics and competitive performance of the supply chain.